ANALISIS NILAI TAMBAH TORTILA RUMPUT LAUT PADA INDUSTRI RISQA MULIA DI DESA OLAYA KABUPATEN PARIGI MOUTONG - Ambo Tang,Hadayani,Rukavina Baksh, Yusmawati Hi (AGROTEKBIS, 2015)
This study aims to determine the income and value added derived from seaweed processing into tortilla seaweed on Risqa Mulia industry in Olaya Village Parigi Moutong Regency. The location determination is done intentionally (purposive) with the consideration that the Risqa Mulia industry is the only industry that produces tortilla seaweed in Olaya Village Parigi Moutong Regency. This study was conducted in November 2014. Respondent committed intentionally (purposive). Respondents in this study is as much as 6 people consisting of 1 people leadership and 5 employees. Collecting data in this study consist of primary data and secondary data. The analysis consists of two analyzes : analysis of income and value added analysis method according to Tarigan. The results showed that (1) Income tortilla seaweed on Risqa Mulia industry November 2014 at Rp. 2.051.636, (2) Value added tortilla seaweed on Risqa Mulia industry at Rp. 42.742,417 / kg of raw materials used in terms of the added value of the benefits available in 1 kg of raw material usage.